Gene-profiling power supply for athletes of high qualification. The example of biathlon - Kruchynsky, N.; Lebed, T.; Marinich, V.; Slyj, E.; Shepelevich, N.; Yevdaliuk, S. (Sporto Mokslas-Sport Science, 2018)
In the presented article, the possibilities of carrying out the gene-profiling of the power supply process in biathlon, as an example, are considered. The results of genotyping of 31 biathlon-athletes of high qualification on a panel of six polymorphic markers of genes, involved in energy supply processes (ACE, PPARA, PPARGC1A, PPARD, PPARGC1B, and PPARG2),was given. The research was conducted in compliance with necessary ethical criteria: obtaining informed consent from athletes and ensuring the confidentiality of personal information. In the examined group of biathlon-athletes, the prevalence of allele frequencies was observed: 67.74% D allele of the ACE gene; 77.42% G allele of the PPARA gene; 56.45% Ser allele of the PPARGC1A gene; 74.20% T allele of the PPARD gene; 95.16% C allele of the PPARG2 gene;100.00% C allele of the PPARGC1B gene. Establishing the genetic potential of each athlete allows determining or refining the molecular mechanisms of inheritance and expanding the theoretical and methodological basis of the process of sports training. At the same time, having determined the differences in the distribution of genotypes in groups of highly qualified athletes, engaged in various sports, it is possible to carry out with confidence the genetic prognosis of success in the group of reserve athletes. Based on the results of earlier conducted research, analysis of the world experience - an algorithm for managing